Rubidium Efflux Assay for the Determination of Calcium Activated Potassium Channel Activity (American International Journal of Biology and Life Sciences, 2020)
Rubidium efflux assay using flame atomic absorption spectrometry is employed in analyzing potassium channel activity. Calibration using standards of known R  concentrations (10 - 100µM) in tubes was done at the beginning and end of each analysis. R  standard curves were constructed from the data obtained from the analysis of the R standards in both the tubes and 96 well plates. HEK293 cells expressing the alpha subunit of BK channel were incubated with R  for 4 hours after which the cells were washed and then treated with higher concentrations of KBS (50mM / 80mM) or NS1619 (0.003 - 100µM) for 10 minutes. The supernatant was removed and the cells lysed with 0.1%v/v triton. The percentage efflux was then determined from values obtained after analyzing the supernatant and lysate using flame atomic absorption spectrometer. The results showed that there was consistency during each analysis as the R  standard curves constructed from the data obtained overlapped with no significant difference indicating precise calibration and internal validation. For the loaded cells (un-treated), the average concentration of R   in the supernatant was 14.47µM while that in the lysate was 56.24µM and statistical analysis showed there was a significant difference with p